Environmental and Ecological Risk Assessment of Trace Metal Contamination in Mangrove Ecosystems: A Case from Zhangjiangkou Mangrove National Nature Reserve, China. (4th October 2016) - Wang, Jun; Du, Huihong; Xu, Ye; Chen, Kai; Liang, Junhua; Ke, Hongwei; Cheng, Sha-Yen; Liu, Mengyang; Deng, Hengxiang; He, Tong; Wang, Wenqing; Cai, Minggang
Abstract : Zhangjiangkou Mangrove National Nature Reserve is a subtropical wetland ecosystem in southeast coast of China, which is of dense population and rapid development. The concentrations, sources, and pollution assessment of trace metals (Cu, Cd, Pb, Cr, Zn, As, and Hg) in surface sediment from 29 sites and the biota specimen were investigated for better ecological risk assessment and environmental management. The ranges of trace metals in mg/kg sediment were as follows: Cu (10.79–26.66), Cd (0.03–0.19), Pb (36.71–59.86), Cr (9.67–134.51), Zn (119.69–157.84), As (15.65–31.60), and Hg (0.00–0.08). The sequences of the bioaccumulation of studied metals are Zn > Cu > As > Cr > Pb > Cd > Hg with few exceptions. Cluster analysis and principal component analysis revealed that the trace metals in the studied area mainly derived from anthropogenic activities, such as industrial effluents, agricultural waste, and domestic sewage. Pollution load index and geoaccumulation index were calculated for trace metals in surface sediments, which indicated unpolluted status in general except Pb, Cr, and As.